2020
DOI: 10.1136/jitc-2020-000613
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of commonly used solid tumor targeted gene sequencing panels for estimating tumor mutation burden shows analytical and prognostic concordance within the cancer genome atlas cohort

Abstract: BackgroundTumor mutation burden (TMB) is a biomarker frequently reported by clinical laboratories, which is derived by quantifying of the number of single nucleotide or indel variants (mutations) identified by next-generation sequencing of tumors. TMB values can inform prognosis or predict the response of a patient’s tumor to immune checkpoint inhibitor therapy. Methods for the calculation of TMB are not standardized between laboratories, with significant variables being the gene content of the panels sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 41 publications
7
8
0
2
Order By: Relevance
“…Interestingly, a previous study confirmed that higher TMB as estimated by a CGP is associated with a favorable prognosis and predicts the clinical benefits of ICB therapy [ 15 , 29 ]. Moreover, in the absence of checkpoint inhibitor treatment, cancer patients with higher TMB tend to have adverse outcomes [ 30 ], which is consistent with our findings, thus, it may also indicate that higher panel-TMB might be an adverse prognostic factor for DLBCL. To elucidate the factors that interact with TMB, we further stratified patients based on tumor burden-related clinical parameters, including extranodal involvement, LDH, IPI, and stage, and the results demonstrate that in cases with higher tumor burden, more extranodal involvement sites, elevated LDH, advanced stage, higher IPI score, and higher mutation burden might be worse for the prognosis of these subsets of cases, indicating that mutation burden and tumor burden act as doubly impaired factors for survival.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, a previous study confirmed that higher TMB as estimated by a CGP is associated with a favorable prognosis and predicts the clinical benefits of ICB therapy [ 15 , 29 ]. Moreover, in the absence of checkpoint inhibitor treatment, cancer patients with higher TMB tend to have adverse outcomes [ 30 ], which is consistent with our findings, thus, it may also indicate that higher panel-TMB might be an adverse prognostic factor for DLBCL. To elucidate the factors that interact with TMB, we further stratified patients based on tumor burden-related clinical parameters, including extranodal involvement, LDH, IPI, and stage, and the results demonstrate that in cases with higher tumor burden, more extranodal involvement sites, elevated LDH, advanced stage, higher IPI score, and higher mutation burden might be worse for the prognosis of these subsets of cases, indicating that mutation burden and tumor burden act as doubly impaired factors for survival.…”
Section: Discussionsupporting
confidence: 89%
“…In a study of 35 patients with melanoma treated with ipilimumab and nivolumab, TMB was significantly higher in responders than in non-responders and TMB-high status (> 23.1 Mut/Mb) was associated with a survival benefit versus TMB-low or TMB-intermediate (TMB ≤ 23.1 Mut/Mb) [ 32 ]. Several retrospective studies across different tumor types, but in particular melanoma and NSCLC, have also reported that higher TMB is correlated with improved response rates and survival times with immune checkpoint inhibitor therapy [ 33 ]. A positive correlation between TMB and improved response to checkpoint blockade is not unexpected, given the higher the mutational load the higher the probability that neoantigens are presented on the tumor surface.…”
Section: Mechanisms Of Resistance and Drivers Of Response—sessionmentioning
confidence: 99%
“…However, WES is not practical in routine clinic, and studies have shown that TMB obtained from targeted next-generation sequencing (NGS) panels has high concordance with WESderived TMB and significant predictive value for immunotherapy efficacy. [6][7][8] Hematologic cancers generally have lower TMBs than solid tumors. The most common aggressive B-cell lymphoma diffuse large B-cell lymphoma (DLBCL) has a significantly higher TMB than chronic lymphocytic leukemia and acute myeloid leukemia as measured by WES (median, ~3 vs ~0.8 and 0.37 non-silent coding mutations per Mb, respectively).…”
Section: Introductionmentioning
confidence: 99%